2002
DOI: 10.1136/adc.86.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Hermansky-Pudlak syndrome: infrequent bleeding and first report of Turkish and Pakistani kindreds

Abstract: Hermansky-Pudlak syndrome (HPS) is a rare disorder characterised by oculocutaneous albinism, a bleeding tendency, and lipofuscinosis. This retrospective study reviews the clinical history and haematological features of 23 cases of HPS. Information was gathered from patient notes and by direct interview. Thirteen of the 23 children were of Turkish origin, 12 being members of four kindreds from the Turkish/Kurdish border. Four children originated from Pakistan. Haemorrhage was uncommon; two experienced significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
2
20
0
1
Order By: Relevance
“…There is a need for more information on the PFA‐100 CT in congenital platelet disorders as reported studies (summarized in Table 1) have evaluated relatively small numbers of individuals (<50/study) with varying mixes of characterized disorders [8,14,16,19,34,49,50,52,53]. The estimated PFA‐100 CT sensitivity to platelet disorders has ranged from 24% [52], for a recent prospective study of previously undiagnosed patients identified to have platelet secretion defects, to values of 80% and higher, for studies that included previously diagnosed cases and more severe platelet disorders [8,16,34,50,53] or that had a more limited sample size [19]. Differences in study designs (prospective or retrospective case identification and selection, variable inclusion of drug‐induced platelet dysfunction) are likely reasons for the differences in sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for more information on the PFA‐100 CT in congenital platelet disorders as reported studies (summarized in Table 1) have evaluated relatively small numbers of individuals (<50/study) with varying mixes of characterized disorders [8,14,16,19,34,49,50,52,53]. The estimated PFA‐100 CT sensitivity to platelet disorders has ranged from 24% [52], for a recent prospective study of previously undiagnosed patients identified to have platelet secretion defects, to values of 80% and higher, for studies that included previously diagnosed cases and more severe platelet disorders [8,16,34,50,53] or that had a more limited sample size [19]. Differences in study designs (prospective or retrospective case identification and selection, variable inclusion of drug‐induced platelet dysfunction) are likely reasons for the differences in sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…healthy controls compared with patients with higher VWF levels), aspirin dosage and formulation effects [67], and pretest variables, such as the citrate concentration used for sample collection [24,69]. It is important to recognize that the aspirin/NSAID pattern of PFA‐100 CT abnormalities (CEPI prolonged, CADP normal) is not specific for drug‐induced platelet dysfunction as similar abnormalities occur with congenital platelet disorders (Table 1) [4,8,14,34,50,51,53] and with consumption of flavonoid‐rich foods [48]. When NSAIDs are discontinued, PFA‐100 CT abnormalities revert by 6 days with aspirin [70] and by 24 h with ibuprofen [71].…”
Section: Resultsmentioning
confidence: 99%
“…One of the other five patients with HPS‐5 is of Turkish descent, like our patient. In 2002, the clinical features of 13 children with HPS originating from five families of Turkish descent were described (18). As far as we know mutation analysis of these patients has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study also demonstrated that the PFA‐100 ® was more sensitive than the BT to VWD and platelet defects in a paediatric population (Cariappa et al , 2003). Although the overall sensitivity of the PFA‐100 ® to VWD seems to be excellent when compared with the BT, there have been reported differing sensitivities to type I VWD (Harrison et al , 2002a, b; Liesner et al , 2004; Quiroga et al , 2004a). Borderline VWF levels on either side of laboratory cut‐offs can sometimes give normal or abnormal CTs.…”
Section: The Pfa‐100® Versus the Bleeding Time As A Screening Toolmentioning
confidence: 99%